The role of organic fertilization and arbuscular mycorhizal fungi inoculation on sweet corn growth on rasau series soil | IJAAR - Rawayau, Haruna, Yahaya (My University, 2022)
The objective of this research was to determine the effect of organic and bio fertilization on the growth performance of corn planted on Rasau series soil. A factorial experiment of 5 x 2 Randomised Complete Block Design replicated 4 times was conducted at the glasshouse of Universiti Malaysia Terengganu. The factors include organic manure at 5 levels OM1 (control), OM2 (chicken manure), OM3 (cattle manure), OM4 (horse manure) and OM5 (biochar), and arbuscular mycorrhizal Fungi at 2 levels M1 (with) and M2 (without), the variables measured were plant height, stem girth, leaf height, leaf number, leaf length, leaf width and leaf area at 2, 4, 6 and 8 weeks after planting (WAP). The data collected were analyzed using Analysis of Variance (ANOVA) with Statistical Analysis System (SAS) and means separated using Duncan’s Multiple Range Test at p<0.05. The growth performance of the test crop (sweet corn) in this experiment was significant in the measured parameters with chicken manure (OM2) under mycorrhizal inoculation (M1). The result of this study showed chicken manure when inoculated with AMF can boost sweet corn production on Rasau series soil
Keywords: AMF; IJAAR; INNSPUB; Mycorrhizal inoculation; Organic fertilization; Rasau series soil